Teachers’ Psychosocial Characters and Students’ Achievement in Basic Science and Technology - Afuwape, Moses Olanrewaju; Akanbi, Deborah (NIU Journal of Social Sciences, 2023)
Teachers plays an important role in the education of students in acquiring knowledge needed in the society they intend to live. The National Policy of Education (1981), Section 5, 32a and b dialogue on the acquisition, development and inculcation of the proper value-orientation for the survival of the individual and society; the development of the intellectual capacities of individuals to understand and appreciate their environments. It is in the view of this intention that this study aimed at examining influence of teachers’ self-efficacy, motivation and pedagogical competence on student’s academic achievement in Basic Science and Technology (BST) in Ijebu-North Local Government of Ogun State, Nigeria. The study adopted a descriptive survey research. Simple random sampling technique was used to select 150 BST students from 3 schools in Ijebu North Local Government of Ogun State. The study made use of validated BST achievement test and questionnaire for self-efficacy, motivation and pedagogical competence. The results of variables of study showed significant outcomes and recommendations were made accordingly in the study i.e emphasis should be laid on teachers’ pedagogical competence in terms of training for teaching effectiveness while factors of motivation should be given adequate attention. Keywords: Psychosocial characters, self-efficacy, motivation, pedagogical competence, behaviours, communication skill, conceptual clarity, personality and psychological equanimity, achievements, Basic Science and Technology